2019
DOI: 10.1002/ece3.4998
|View full text |Cite
|
Sign up to set email alerts
|

High throughput measure of diversity in cytoplasmic and nuclear traits for unravelling geographic distribution of rosemary

Abstract: In the present work, variability of both cytoplasmic and nuclear microsatellite traits was investigated with the aim of characterizing a set of rosemary germplasm resources ( Salvia rosmarinus ). Most of the materials were collected in Italy and France. High‐resolution melting curves were compared each other computing their Euclidean distances and estimating the differences within their principal component as a measure of genetic diversity. Mantel correlation results combined to linear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Rosemary presents a variety of different habitus types, morphological traits, flower colours and aromatic properties [80]. Our study confirms results reported by Flamini et al [81], who, in a recent study on the evaluation of the agronomic and production characteristics of two rosemary biotypes, state that the best performances are produced by biotypes with an erect habitus.…”
Section: Discussionsupporting
confidence: 91%
“…Rosemary presents a variety of different habitus types, morphological traits, flower colours and aromatic properties [80]. Our study confirms results reported by Flamini et al [81], who, in a recent study on the evaluation of the agronomic and production characteristics of two rosemary biotypes, state that the best performances are produced by biotypes with an erect habitus.…”
Section: Discussionsupporting
confidence: 91%
“…These studies, and most others applying HRM to non-model organisms (Dang et al, 2012;Li et al, 2012;Radvansky et al, 2011), set out to develop HRM primers having prior knowledge of the nucleotide variation under analyses. Unfortunately, such knowledge is generally not available for the study of non-model organisms and the application of HRM for detecting and genotyping of novel genetic variation in wild populations is still rare (Nunziata et al, 2019;Sillo et al, 2017). High Resolution Melt analysis appears to be an underutilized resource by phylogeographers.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean herb S. jordanii is one of the potential medicinal herbs especially against the fungal infections due to its rich source of anti-fungal components present [7][8][9][10]. S. jordanii was previously described as rosemary but the recent studies based upon its DNA sequencing classified into Salvia family [11]. The leaves of S. jordanii were collected and dried to extract the essential oil required for this work to check its antifungal activities against the collected specimens [12][13][14].…”
Section: Introductionmentioning
confidence: 99%